FACTORS AFFECTING SUCCESS BIDDING EVENT AT PT. ASTRINDO CONVEX - Kansa Amran, Shifa Adinda; Auliya, Anisatul; Sari, Dhiny Anjung (UI Scholars Hub, 2021)
Bidding is an offer letter for MICE (meeting, incentive, convention, and exhibition) organizers made by MICE companies such as Event Organizers to compare prospective clients to select the Event Organizer to be selected as the host of the event. The purpose of this study is to find out what factors influence the success of a bidding event and how to succeed and win a bidding event. This research is descriptive research with a qualitative approach. The data used in this study were obtained utilizing observation, interviews, and literature study. This research was conducted during the Field Work Practice Program at PT. Astrindo Convex. The results of this study indicate that the factors that influence the success of bidding events are by paying attention to the bidding stages, namely, bidding requirements, bidding preparation, bidding implementation strategies, and the key to success implemented by PT. Astrindo Convex in bidding, namely by making video documentation to complete the portfolio, prioritizing 3 event sectors, maintaining relationships with clients, and each event team preparing things that need to be prepared during bidding such as communication techniques, product knowledge, negotiation techniques, and appearance.